Portraits of Catania City in The Civitates Orbis Terrarum of Braun and Hogenberg: the “local” model (Sixteenth Century) - Enrico Iachello (Revista Movimentos Sociais e Dinâmicas Espaciais)
This work is part of a research project on the processes of the formation of urban identities. It attempts to reconstruct the role that images and descriptions have played in the process, using Catania as a case study. In this article we will examine, by way of municipal history and iconography, the process of constructing a “portrait” of the city (a map/view) linked to the need to “construct” an all-encompassing view, an identity: a map-view published in Amsterdam in 1598 and included in the 5th volume of Braun and Hogenberg’s Civitates Orbis Terrarum, clearly drew on a “local” model, a map printed on behalf of the Catanian Antonio Stizzia in Rome in 1592.